Effect of Trataka on the Shooting Performance of District Level Shooters: Impact of Trataka Practice on District Level Shooters' Performance (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The researcher frames a research question on effect of trataka on the shooting performance of the district level children. For the purpose of the study, the researcher selected 30 children aged 13±2 years. These randomly selected participants were randomly allocated to the groups formed i.e. experimental group and control group. The independent variable was trataka practice. The participants practiced trataka for 12 week thrice a week. The participants gazed at flame of candle in a dark room for 15 minutes per session. The data was collected pre and post getting the treatment. For the data analysis ANCOVA technique was employed to get the results. Based on the results of the study, the researcher has concluded that there is a positive and significant effects on shooting performance due to the trataka practice.